An Appaisal of the Practice of I’tikaf in Selected Mosques in Ilorin Metropolis - Dr. Ali Miqdad Ali; Ibrahim Qadri (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract Ictikāf is one of the common spiritual practices in Islam. It is a spiritual retreat, usually done in a central Mosque where jum’ah is being performed during the last ten days of Ramadan with the intention of moving closer to Allah. The research aims to examine the concept of Ictikāf as mentioned in the Glorious Qu’ran and Sunnah as well as the perceived abuse of the sacred exercise among contemporary Muslims in Ilorin. Analytical and descriptive research methods were adopted in this study. Analytical method was utilized to analyze the prophetic Ictikāf while observation method was used to gather information about the practices, motives and behavior of people in selected Itikaf centres in Ilorin Metropolis. Interview was conducted with volunteers who are actively involved in practice and planning for Itikaf in Ilorin. it was found that despite the awareness of some Muslims on the prophetic Ictikāf, they still involved abusing and violating the rules and regulations of Ictikāf. This study therefore, suggested that before someone could engage in the practice of Ictikāf, he must know the etiquettes, conditions, rules, and regulations governing its practice, and uphold a decent and upright behaviors throughout the period.